A benefit-cost analysis of the Tulsa universal pre-K program - Timothy J. Bartik; William T. Gormley; Jonathan A. Belford; Sara Anderson (W.E. Upjohn Institute for Employment Research, 2016)
In this paper, benefits and costs are estimated for a universal pre-K program, provided by Tulsa Public Schools. Benefits are derived from estimated effects of Tulsa pre-K on retention by grade 9. Retention effects are projected to dollar benefits from future earnings increases and crime reductions. Based on these estimates, Tulsa pre-K has benefits that exceed costs by about 2-to-1. This benefit cost ratio is far less than the much higher benefit-cost ratios (ranging from 8-to-1 to 16-to-1) for more targeted and intensive pre-K programs, such as Perry Preschool and the Chicago Child-Parent Center (CPC) program. Comparing benefit-cost results from different studies suggests that our more modest estimates are due to two factors: 1) smaller percentage effects of pre-K on future earnings and crime in Tulsa than in Perry and CPC, and 2) smaller baseline crime rates in Tulsa than in the Perry and CPC comparison groups.
Keywords: I28; I26; H43; 330; Universal pre-K; benefit-cost analysis; grade retention; crime reduction effects of education; increased earnings effects of education